2021
DOI: 10.1002/2211-5463.13074
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a four‐lipid metabolism gene signature for diagnosis of pancreatic cancer

Abstract: Abnormal lipid metabolism is closely related to the malignant biological behavior of tumor cells.Such abnormal lipid metabolism provides energy for rapid proliferation, and certain genes related to lipid metabolism encode important components of tumor signaling pathways. In this study, we analyzed pancreatic cancer datasets from The Cancer Genome Atlas (TCGA) and searched for prognostic genes related to lipid metabolism in the Molecular Signature Database. A risk score model was built and verified using the GS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 50 publications
(63 reference statements)
0
9
0
Order By: Relevance
“…Hilvo et al (2011) demonstrated that the lipids in the breast cancer tissue were correlated with tumor progression and patient survival. Moreover, previous studies have demonstrated that lipid metabolism related genes (LMRGs) had potent prognostic potential in multiple types of tumors, including ovarian carcinomas (Zheng et al, 2020), lung adenocarcinoma (LAUD) (Li et al, 2020), pancreatic cancer (Ye et al, 2021), hepatocellular carcinoma (HCC) (Hu et al, 2020), renal cell carcinoma (RCC) (Bao et al, 2019) and diffuse gliomas (Wu et al, 2019). As such, targeting lipid metabolism has been regarded as a novel therapeutic strategy for tumor treatment (Visweswaran et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Hilvo et al (2011) demonstrated that the lipids in the breast cancer tissue were correlated with tumor progression and patient survival. Moreover, previous studies have demonstrated that lipid metabolism related genes (LMRGs) had potent prognostic potential in multiple types of tumors, including ovarian carcinomas (Zheng et al, 2020), lung adenocarcinoma (LAUD) (Li et al, 2020), pancreatic cancer (Ye et al, 2021), hepatocellular carcinoma (HCC) (Hu et al, 2020), renal cell carcinoma (RCC) (Bao et al, 2019) and diffuse gliomas (Wu et al, 2019). As such, targeting lipid metabolism has been regarded as a novel therapeutic strategy for tumor treatment (Visweswaran et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Emerging evidence also indicates that aberrant lipid metabolism is involved in drug resistance during cancer treatment ( Iwamoto et al, 2018 ; Cao, 2019 ). Previous studies have reported that risk signatures derived from lipid metabolism-associated genes (LMAGs) exhibit potent capability in predicting the prognosis of various tumors, including serous ovarian carcinomas ( Zheng et al, 2020 ), clear cell renal cell carcinomas ( Zheng et al, 2020 ), pancreatic cancer ( Ye et al, 2021 ), lung adenocarcinomas ( Li et al, 2020 ), and diffuse gliomas ( Li et al, 2020 ). However, the prognostic value of LMAGs in patients with BRCA remains largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…8 B). Aberrant activation of de novo lipid synthesis is one of the key characteristics that distinguishes tumor cells from normal cells, as de novo lipid synthesis is rare in normal cells, whereas the majority (~ 90%) of fatty acids in tumor cells are formed by de novo synthesis [ 16 , 17 ]. ACACA, FASN and SCD are key enzymes in de novo lipid synthesis [ 15 , 18 ].…”
Section: Resultsmentioning
confidence: 99%
“…In contrast to normal cells, tumor cells are usually characterized by significantly higher lipid uptake and synthesis [ 5 , 6 , 9 ]. Particularly, normal cells typically do not undergo de novo lipid synthesis, whereas approximately 90% of fatty acids are de novo synthesized in tumor cells [ 16 , 17 ]. Studies have shown that abnormal lipid metabolism is directly related to the development and metastasis of malignant tumors [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%